Evaluating the Operational Performance of Community-Based Tourism Enterprises and their contribution to community Conservation outcomes around Bwindi Impenetrable National Park - Monica Kyarikunda; Grace Kagoro-Rugunda; Tom Ogwang (Journal of Tourism and Hospitality Management, 2026)
Although Community Based Tourism Enterprises (CBTEs) significantly support conservation and sustainable livelihoods around Bwindi Impenetrable National Park, over 30 years they have undergone major changes in management, population, market demand and tourist numbers, whose effect on the performance of CBTEs remains unevaluated. There is a danger of overreliance of communities on CBTEs, which creates a syndrome of complacency in communities to only look at biodiversity as their only source of livelihood, hindering their innovation in terms of income generation. This may lead to communities relying on the park resource as the only source of innovation for income or survival, putting a threat to the intended conservation outcomes. This study evaluated the performance of CBTEs operating within the four sectors of Bwindi Impenetrable National Park (BINP), Buhoma, Ruhija, Rushaga, and Nkuringo, to determine the extent to which they have lived up to their mandate of supporting livelihoods and enhancing conservation outcomes. Data were collected through questionnaire surveys with CBTE registered members, CBTE employees, Managers; in-depth interviews with UWA officials, Ministry of Tourism officials, local government officials, as well as NGO representatives and Focus Group Discussions (FGDs) with CBTE participants ranging from 6 to 12 participants. Community-Based Tourism Enterprises (CBTEs) around BINP exemplify a sustainable development model that integrates livelihood improvement, social cohesion, and conservation promotion. The findings show a significant relationship between CBTE performance and conservation outcomes like providing socio-economic and environmental benefits, which strengthen local support for conservation, supporting the community's drive to protect natural resources. To enhance their impact, strategic interventions are needed to increase the number of community-owned accommodation-based enterprises, capacity building to improve service quality, strengthening collaborations between CBTEs, tour operators and NGOs for value chain connections to increase tourist flow, leveraging digital marketing to increase visibility of CBTEs for better outcomes.
Keywords: Bwindi Impenetrable National Park; Sustainability; Community-Based Tourism Enterprises; Community Conservation outcomes; Sustainable tourism